Semiconductor device physics and simulation - Yuan, J. S. (Plenum Press, 1998)
This book provides comprehensive coverage of device simulation and analysis for various modem semiconductor devices. It will serve as a reference for researchers, engineers, and students who require in-depth, up-to-date information and understanding of semiconductor device physics and characteristics. The materials of the book are limited to conventional and mainstream semiconductor devices; photonic devices such as light emitting and laser diodes are not included, nor does the book cover device modeling, device fabrication, and circuit applications.